Antioxidant and Antiproliferative Potential of Solvent-Extracted Arachis hypogaea L. Skins from Malaysian Cultivar - Majed Ahmed, Al-Mansoub; Hussein M., Baharetha; Mohamad Taleb, Agha
Arachis hypogaea L. (peanut), a member of the Fabaceae family, is widely cultivated and consumed in Malaysia. Peanut skin is gaining interest as an agro-waste resource due to its rich antioxidant content and potential application in functional food development. This study was carried out to investigate the antioxidant capacity and antiproliferative activity of peanut skin extracts obtained using three different solvents. The extracts were first screened for antioxidant activity, and the most active extract was subsequently tested against colon (HCT-116), breast (MCF-7), and lung (A549) cancer cell lines using the MTT assay. The methanol extract of peanut skin exhibited the highest antioxidant activity, with a total phenolic content (TPC) of 269.06 μg GAE/mg and total flavonoid content (TFC) of 10.66 μg QE/mg, exceeding those of the n-hexane and chloroform extracts. This trend was further supported by strong antioxidant activity in DPPH, ABTS, and FRAP assays. At 100 μg/mL, the methanol extract inhibited the growth of A549, MCF-7, and HCT-116 cells by 60.21%, 23.84%, and 17.75%, respectively. These findings support the potential application of peanut skin methanol extract as a natural source of bioactive compounds with promising anti-lung cancer properties. Further investigation, including detailed compound isolation and mechanistic studies, is ongoing to substantiate these preliminary findings.